A Picture of Hope: 30-year Journey – Postocular Trauma and Intraocular Lens - Lipi Mittal; Srishty Sen (Delhi Journal of Ophthalmology)
We report a consequence of a 3 decades old complicated cataract surgery post ocular trauma wherein a multipiece IOL was implanted in the anterior chamber with ends of haptics directed into the sulcus via PI, thus reducing the chances of future development of glaucoma and corneal decompensation and enabling the IOL to go over 3 decades without causing any trouble to the patient.